Adaptasi Dan Validasi Instrumen KIDSCREEN-27 Versi Bahasa Indonesia - Utari, Dewi; Lestari, Ratna (Window of Health : Jurnal Kesehatan, 2020)
The changes that occurred to cancer patients have affected the quality of life of both the patients and their family including the children. However, the tool to assess the adolescent quality of life is rarely found in the Indonesian version. Therefore, this study aimed to adapt and validate the instrument KIDSCREEN-27 into the Bahasa Indonesia version. This research was applied to a cross-cultural adaptation procedure which consists of five-phase. First is a translation, synthesis process, back translation, expert analysis, and the last is reliability. The research was involved 30 adolescents aged 11 – 18 years old who have a mother with cancer. The cancer patients were derived from the hospital of RSUD Panembahan Senopati Bantul. The data was obtained from January – February 2019. This was used as a purposive sampling technique along with the content validity index (CVI) and reliability test which performed Alfa Cronbach. The result of the content validity index (CVI), I-CVI and S-CVI from three different experts was 1.00. Meanwhile, the value of Alpha Cronbach’s was 0.893. The internal consistency of 5 domains in the range value of α 0.654 – 0.840 with the highest is family and free time and the lowest is friends. The instrument of KIDSCREEN -27 Bahasa Indonesia version is valid and reliable, thus, is able to assist the health care provider to examine the adolescent’s quality of life.